2015
DOI: 10.1634/theoncologist.2014-0361
|View full text |Cite
|
Sign up to set email alerts
|

Age-Stratified Risk of Unexpected Uterine Sarcoma Following Surgery for Presumed Benign Leiomyoma

Abstract: Background. Estimates of unexpected uterine sarcoma following surgery for presumed benign leiomyoma that use agestratification are lacking. Patients and Methods. A retrospective cohort of 2,075 patients that had undergone myomectomy was evaluated to determine thecase incidence ofunexpecteduterinesarcoma. Anaggregate risk estimate was generated using a meta-analysis of similar studies plus our data. Database-derived age distributions of the incidence rates of uterine sarcoma and uterine leiomyoma surgery were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 14 publications
4
42
1
1
Order By: Relevance
“…The risk of unexpected LMS increased steadily in ages from the 40s to the 50s (0.11% and 0.36%, respectively), whereas the risk of unexpected ESS decreased steadily in the same period (0.58% and 0.24%, respectively). The risk trend of unexpected LMS and ESS was in accordance with the result of the study by Brohl et al 21 It is obvious that age stratification significantly affects the risk prediction for uterine sarcoma.…”
Section: Preoperative Evaluationsupporting
confidence: 88%
See 1 more Smart Citation
“…The risk of unexpected LMS increased steadily in ages from the 40s to the 50s (0.11% and 0.36%, respectively), whereas the risk of unexpected ESS decreased steadily in the same period (0.58% and 0.24%, respectively). The risk trend of unexpected LMS and ESS was in accordance with the result of the study by Brohl et al 21 It is obvious that age stratification significantly affects the risk prediction for uterine sarcoma.…”
Section: Preoperative Evaluationsupporting
confidence: 88%
“…Recently, Brohl et al 21 presented that the risk of unexpected uterine sarcoma seemed to be age related and reported that the peak incidences of all uterine sarcoma, LMS, and ESS were in the perimenopausal age range of 45 to 54 years, with ESS peaking in incidence at a slightly younger age than LMS based on a meta-analysis. In the present study, patients with unexpected uterine sarcomas were all in their 40s and 50s and 12 (66.67%) patients were at 45 to 54 years.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…Pre-operatively it is difficult to differentiate benign leiomyomas from malignant LMS and so the surgical approach should be planned accordingly; laparoscopic morcellation is contraindicated for uterine sarcoma due to higher risk of recurrence and metastasis [121123]. The risk of inadvertent morcellation of a uterine sarcoma increases significantly with age [124], and the US Food and Drug Administration (FDA) released a safety communication concerning the procedure in 2014 [125]. Standard surgical management for non-metastatic disease is total abdominal hysterectomy (TAH) with, or without bilateral salpingo-oophorectomy (BSO).…”
Section: Uterine and Retroperitoneal Sarcomasmentioning
confidence: 99%
“…Ultrasonography is the first‐line investigation of leiomyomas, and their abnormal appearance on ultrasound and increasing size or symptoms, particularly in patients who are postmenopausal or in the setting of medical therapy, require further investigation with magnetic resonance imaging (MRI) to exclude malignancy. The rate of leiomyosarcoma in leiomyomas previously considered benign is thought to be less than 1% 19 . Asymptomatic fibroids do not require treatment, and there are various approaches to manage symptomatic leiomyomas which will depend on the patient's preference; the patient's age and menopause status; the plans for fertility; location, size and number of leiomyomas; and available facilities.…”
Section: Leiomyomasmentioning
confidence: 99%